2022
DOI: 10.3389/fnut.2022.1046800
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biotin intervention on glycemic control and lipid profile in patients with type 2 diabetes mellitus: A systematic review and meta-analysis

Abstract: BackgroundBiotin is a water-soluble vitamin acting as a covalently bound coenzyme in regulating energy production. Previous studies have reported that biotin supplementation may influence blood glucose and lipid level in patients with type 2 diabetes mellitus (T2DM).MethodsWe searched Pubmed, Embase, and Cochrane library databases up to 8th August 2022 for studies examining the effects of biotin supplementation in T2DM patients. Pooled effects were measured by weighted mean differences (WMDs) with 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In a meta-analysis examining the effect of biotin usage on glycemic control and lipid profile in patients with type 2 diabetes mellitus conducted in 2022, it was reported that biotin treatment can reduce fasting blood glucose, total cholesterol, and triglyceride levels [ 13 ]. Also, in a study conducted with twins, it was reported that biotin levels were negatively correlated with triglyceride levels [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis examining the effect of biotin usage on glycemic control and lipid profile in patients with type 2 diabetes mellitus conducted in 2022, it was reported that biotin treatment can reduce fasting blood glucose, total cholesterol, and triglyceride levels [ 13 ]. Also, in a study conducted with twins, it was reported that biotin levels were negatively correlated with triglyceride levels [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The physiological associations between biotin and diabetes have been well-investigated. Numerous in vitro and in vivo studies have demonstrated that biotin could stimulate pancreatic islet glucokinase activity and expression, increase insulin secretion, and induce insulin receptor synthesis in non-diabetic states, whilst considering the significance of biotin as an efficient ameliorator of hyperglycemic status in diabetes [ 117 ]. Although the mechanism of hyperglycemia is different between T1DM and T2DM, biotin plays an important role in glucose homeostasis for both types of diabetes.…”
Section: Vitamin B8 (Biotin)mentioning
confidence: 99%
“…Pharmacologic uses of biotin have been limited to the treatment of conditions such as [40] biotin-responsive basal ganglia disease (100-300 mg/day), inherited metabolic diseases such as biotinidase (5-10 mg/day) and holocarboxylase synthetase deficiencies (30-40 mg/day), and multiple sclerosis (MS) (up to 300 mg/day) [29]. However, recent studies suggest that biotin supplementation can improve the treatment and management of diseases such as inflammatory bowel disease (IBD) [44], obesity [68], and type II diabetes [69].…”
Section: Biotin Interferencementioning
confidence: 99%